Promoting sustainable agriculture through feed-in tariff policy in Pakistan: solar irrigation pumping for enhanced crop diversification - Junaid, Novaira; Akbar, Muhammad Zain; Shah, Azeem Ali (International Water Management Institute, 2024)
This project brief highlights sustainable irrigation methods along with the potential benefits of promoting solar-powered irrigation systems in Punjab, Pakistan. To promote the broad adoption of ecologically sustainable farming methods, the brief stresses the need to create a legislative framework that gives suitable incentives to farmers to improve their living conditions and increase the variety of crops they grow. In this regard, a feed- in tariff (FIT) policy that supports solar irrigation pumps (SIPs) might reduce financial costs and the dependency on nonrenewable fossil fuels, thereby incentivizing farmers to save groundwater resources and sell power back to the grid by implementing a feed-in tariff rate of Rs. 20/kWh for SIPs in Pakistan.